Print and production finishes for packaging - Denison, Edward (RotoVision SA, 2008)
Packaging is an area of design we encounter more than almost any other. Nearly everything we buy is packaged, and design lies at the heart of a package's success. This book is practical guide to the finishes, surface graphics, detailing, and materials available to packaging designers today. It shows, at a glance, the different effects that can be achieved through processes such as embossing, debossing, die-cutting, stamping, molding, and etching.